(untitled) (Bangladesh Veterinarian, 2015)
The present study was conducted to evaluate the effect of different milk replacers on the performance of kids. In a 60-day feeding trial, twenty kids of both sexes (15 days of age and average 1.9 ± 0.4 kg BW) were divided into four groups having five kids in each and were assigned to four treatments: milk replacer prepared using shoti (Curcuma zedoaria) powder (T1), milk replacer prepared using fresh eggs and wheat flower (T2) and milk replacer prepared from skim milk powder (T3). Total DM and milk DM intake were significantly (P<0.001) higher in T1 than T3, T0 and T2 groups. ME and MP intake were significantly (P<0.05) higher in T1 than the other three groups. Average daily gain was significantly (P<0.05) higher in T1 compared to T2 and T3 groups, while control was intermediate. Body weight gain of T2 and T3 group increased up to 5th week and declined thereafter. Feed conversion efficiency did not differ significantly between groups. DM and OM digestibility was significantly (P<0.05) higher in T1 group. N retention (as percentage of N-intake) was lower in T3 group. Costs for T0, T1, T2 and T3 groups were 4.7, 9.0, 36.6 and 4.7 Tk/100g (or 0.054, 0.113, 0.456 and 0.054 /100g) mixed dry milk replacer. Since the supplementation of milk replacer did not affect weight gain, FCR and nutrient utilization, milk replacer was cost-effective. Therefore, shoti and egg + wheat can be fed to goat kids as an alternative to goat milk. DOI: http://dx.doi.org/10.3329/bvet.v31i1.22842 Bangl. vet. 2014. Vol. 31, No. 1, 46-54